Predicting market acceptance of autonomous vehicles - Lopes da Costa, R.; Pereira, L.; Dias, Á.; Gonçalves, R. (International Journal of Business Innovation and Research, 2023)
Nowadays we are facing a digital era submerse in technology. Information technology is embracing every industry, causing significant impacts and leading to considerable adaptations. The distribution industry is no exception. This study aims to collect evidence supporting that distribution channels are still not benefiting from information technologies entire potential. This research proposes to understand and analyse the factors that can influence customer mindset towards technology, either positively or negatively, helping to predict technology acceptance and use more accurately, specifically approaching autonomous vehicles, who promise to revolutionise distribution, particularly in terms of mobility. This research analyses autonomous vehicles growth and predict their impact in a global perspective and objectively in the distribution industry. An online survey was conducted, allowing the collection of most up-to-date information about distribution channels, in terms of efficiency and potentialities and concerns influencing the acceptance and use of this innovative technology.